Studies of variations in insertion cations in Intergrowth Tungsten Bronzes (ITBs) - Sloan, J; Langley, K; Day, E; Meyer, R; Kirkland, A (2004)
The characterisation of a series of intergrowth tungsten bronzes (ITB) of the form MxWO(3) (M = K, Rb and Cs) by the technique of focal series restoration is discussed. Preliminary results with regard to the determination of alkali metal concentrations within the hexagonal tunnels formed within the intergrowth phase are presented. The obtained modulus images provide a basis for direct calculation of M-x tunnel occupancy in the ITB structures from both restored modulus images and multislice simulations.